2013
DOI: 10.1099/vir.0.047787-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathogenesis of a mouse-adapted porcine epidemic diarrhea virus infection in suckling mice

Abstract: A mouse-adapted porcine epidemic diarrhea virus, MK-p10, showed higher neurovirulence in suckling mice than a non-adapted MK strain. There was no difference in virus growth, whereas clear differences between these two virus infections existed in the type of target cells infected, the spread of virus and the cytokine levels produced in the brain. In the early phase of infection, neurons, astrocytes and neural progenitor cells were infected by MK-p10, whereas neural progenitor cells were the only target cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…These viruses traditionally cause diseases in pigs and cats, respectively [40][41]. While previous studies did not label them as zoonotic, an experimental study involving mice suggested the potential for the Porcine epidemic diarrhea virus to cause neuropathogenic effects [42]. This study thus introduces the notion that the Porcine epidemic diarrhea virus, along with the Feline infectious peritonitis virus, might possess the capability to infect a broader range of animals.…”
Section: Discussionmentioning
confidence: 99%
“…These viruses traditionally cause diseases in pigs and cats, respectively [40][41]. While previous studies did not label them as zoonotic, an experimental study involving mice suggested the potential for the Porcine epidemic diarrhea virus to cause neuropathogenic effects [42]. This study thus introduces the notion that the Porcine epidemic diarrhea virus, along with the Feline infectious peritonitis virus, might possess the capability to infect a broader range of animals.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]11 The body weight (BW) of neonatal MMPigs is approximately 400 g, and thus the neonates can be housed in isolation cages designed for rats, 5 so the MMPig might be an effective small animal model for PED and may overcome the disadvantages of using mouse models of PED. 7 In this study, to develop a novel small animal model for PED, we infected a neonatal MMPig with PEDV and pathologically examined the infected pig.…”
mentioning
confidence: 99%